A institucionalização da educação a distância no ensino superior público brasileiro: uma revisão sistemática de literatura - Moreira, Iracema Eliza de Vasconcellos (2021)
This research aims to present a scenario of the publications of academic papers that deal with the Institutionalization of Distance Education in Public Institutions of Brazilian Higher Education. The methodology adopted is the systematic literature review and followed the following phases: collection, filtering, and analysis of texts. The texts were taken from databases of databases of academic papers available at internet: Brazilian Digital Library, Capes Thesis and Dissertations Database, SciELO database, Google Academic and Microsoft Academic. The proposed section for the selection of texts was based on collecting the material that contemplated the expressions "Institutionalization of Distance Education" or "Institutionalization of DISTANCE" in the titles of the works. After completing the filtering, it was possible to group together 29 academic researches, 7 theses and 22 dissertations. For the analysis of the texts, all texts were codification. The coding was made from the choice of the categories of analysis adopted and was facilitated with the use of the software NVivo. The results demonstrate the relevance of the modality of Distance Education in the creation of Technological Centers in Higher Education Institutions, in the training of thousands of students, in the acquisition of knowledge for teaching and in the advances and even setbacks of public policies for EaD. We observed that the theme of the institutionalization of THE in public institutions of higher education still deserves a close look on the part of the academic community, because it has not been exhausted and requires the attention of the State to achieve equivalences of the modality with face-to-face education and to overcome the pedagogical and administrative demands fundamental to the realization of the mission of public institutions for continuous improvement of the quality and expansion of Brazilian education.